SOSIOLOGI LEMBAGA PENDIDIKAN MADRASAH IBTIDAIYAH: STUDI TENTANG KESENJANGAN DIGITAL (DIGITAL DIVIDE) DALAM PEMBELAJARAN DARING DAN LURING PASCA PANDEMI - Restu Darma; Muhammad Hanif (Program Studi Sosiologi, 2026)
This study aims to analyze the post-COVID-19 digital divide phenomenon and the role of the digitalization process in transforming the conventional learning system into a modern one at MIN 1 Banyumas. This study employs a qualitative approach with a descriptive method. Data collection techniques included in-depth interviews, direct observation, and document analysis of informants selected through snowball sampling. The findings indicate that MIN 1 Banyumas successfully overcame these obstacles through strategic adaptation, namely collaborating with Amikom University to develop independent platforms such as Madrasah Digital, CBT, and B-link. This initiative was supported by regular digitalization training for teachers held every three weeks and the